Tackling noncommunicable diseases in Africa through football: The case of Malawi. Issue 1 (28th January 2023) - Kangwerema, Allan; Miggo, Mictum; Harawa, Gracian; Kazanga‐Chiumia, Isabel; Haruna, Usman Abubakar; Safari, Jackson; Lutala, Prosper; Kaunda, John Thumbiko
Abstract: There is evidence that physical inactivity and dietary factors are more common among modifiable risk factors for noncommunicable diseases (NCDs) which are on the rise in Malawi. Football has been shown to have a wide range of health‐related benefits in health education programs, including the promotion of physical activity as a potential intervention in addressing NCDs. In Malawi, few football‐based health promotion programs have been implemented to address NCDs. Among the programs implemented were the Federation Internationale de Football Association 11 for Health initiative which was a school‐based health education program for the youth and the Malawi Ministry of Health's SPORTS FOR HEALTH initiative targeting civil servants. These programs produced significant improvement in physical activity in the participants and also increased their knowledge of both communicable and NCDs. However, these initiatives were not rolled out to many sites across Malawi. As Malawi is tackling rising cases of NCDs, football can be used as a powerful tool in promoting physical activity and it also provides an important platform for the delivery of NCDs' health promotion messages to a wider audience. Such football‐based initiatives must be designed to directly address modifiable risk factors of NCDs. For successful implementation, there must be a good collaboration among the Ministries of Health and Sports, local football leagues, and other stakeholders.